Probing structural requirements for human topoisomerase I inhibition by a novel N1-Biphenyl fluoroquinolone - Delgado, Justine L.; Lentz, Sarah R.C.; Kulkarni, Chaitanya A.; Chheda, Pratik R.; Held, Hailey A.; Hiasa, Hiroshi; Kerns, Robert J. (European journal of medicinal chemistry, 2019)
Fluoroquinolones substituted with N-1 biphenyl and napthyl groups were discovered to act as catalytically inhibitors of human topoisomerases I and II, and to possess anti-proliferative activity in vivo. Structural requirements for these novel quinolones to inhibit catalytic activity of human topoisomerase I have not been explored. In this work novel derivatives of the N-1 biphenyl fluoroquinolone were designed, synthesized and evaluated to understand structural requirements of the C-3 carboxylic acid, C-6 fluorine, C-7 aminomethylpyrrolidine, C-8 methoxy, and the N-1 biphenyl functional groups for hTopoI inhibition. Characterization of each analog for inhibition of hTopoI catalytic inhibition reveals critical insight into structural requirements of these novel quinolones for activity. Additionally, results of DNA binding and modeling studies suggest that N-1 biphenyl fluoroquinolones intercalate between the DNA base pairs with the N-1 biphenyl functional group, rather than the quinolone core, and that this mode of DNA intercalation contributes to inhibition of hTopoI by these novel structures. The results presented here support further development and evaluation of N-1 biphenyl fluoroquinolone analogs as a novel class of anti-cancer agents that act through catalytic inhibition of hTopoI. [Display omitted] •Novel quinolones act as catalytic inhibitors of hTopoI.•C-7 amine required for hTopoI catalytic inhibition.•N-1 biphenyl functional group intercalates between DNA base pairs.•Mechanism of DNA intercalation by N-1 biphenyl fluoroquinolones contributes to hTopoI inhibition.•Novel hTopoI inhibitors that do not increase DNA breaks.